The Relationship of Sociodemographic Factors with Near-miss and Missed Cases in Educational and Affiliated Hospitals in Makassar from 2019 to 2020 - Indah Ria Rezeki Meirisa; Elizabet C Jusuf; Nasrudin Mappaware (Faculty of Medicine, Hasanuddin University., 2022)
Introduction: Maternal mortality remains a critical issue in achieving optimal health status. Evaluation through near-miss cases provides valuable data about morbidity to monitor the quality of obstetric services, which can be used to estimate the incidence of life-threatening obstetric complications. A study reported that the incidence of near-miss in pregnant women had a significant relationship with various non-medical factors, included sociodemographic factors. Therefore, this study aims to examine the relationship of sociodemographic factors with near-miss and missed cases. Methods: This analytic retrospective study conducted in Educational and affiliated hospitals in Makassar. Data were retrieved from the obstetric referral registry from 2019 to 2020. Sociodemographic factors of interest include diagnosis, gestational age, maternal age, referral status, maternal parity, and economics. Results: A total of 156 near-miss and missed cases were obtained from January 1, 2019, to December 31, 2020. There was no significant relationship between maternal age (p=0.675), gestational age (p=0.38), parity (p=0.24), economic status (p=0.73), educational background (p=0.85), and referral status (p=0.16) with maternal near-miss and missed cases. Conclusions: There was no significant relationship between sociodemographic characteristics and maternal near-miss and missed cases in Educational and affiliated hospitals in Makassar from 2019 to 2020. More studies are needed to evaluate other factors associated with near-miss and missed cases.